Temporal and spatial variability of carbon cycling in a subarctic landscape - Johansson, Torbjörn (Department of Physical Geography and Ecosystem Science, Lund University, 2006)
This thesis deals with the carbon balance in a subarctic landscape at different temporal and spatial scales. Its focus is mainly on the peatland and mountain birch forest (Betula pubescens ssp. czerepanovii) ecosystems within the Abisko area in northernmost Sweden. This is an area with a temperature close to the 0 OC mean annual isotherm. The area has during the last 30 years experienced a limited but important warming trend. The warming has particular importance for the stability of the peatland ecosystems. A retrospective analysis of vegetation change in the thesis builds upon research pursued during the Swedish Tundra Biome project within the International Biological Programme (IBP) in the 1970s. The thesis also extends the research to the mountain birch forest, an ecosystem where until now very little carbon exchange studies have been conducted. By chance, an opportunity arose to monitor the effects on carbon cycling of a severe insect outbreak (Epirrita autumnata) in the birch forest. Subsequently an initial attempt to budget carbon exchanges and transfers in the whole of a composite subarctic landscape, the Lake Torneträsk catchment was made. During the thirty years passing between the IBP project and now the wet sites with mostly graminoid plant species on the Stordalen mire have increased concurrently with a loss of hummock areas underlain by permafrost. At the same time lichens have increased and evergreen dwarf shrubs as Empetrum hermaphroditum and mosses as Dicranum elongatum have decreased in their abundances. It is suggested that the increase in wet areas is dependent on permafrost collapse. The vegetation change on the hummocks is mainly dependent on earlier snowmelt with resulting frost drought. In connection with the vegetation change the carbon balance of the Stordalen mire has changed. It is estimated that the overall net uptake of C in the vegetation and the release of C by heterotrophic respiration might have increased, resulting in increases in both the growing season atmospheric CO2 sink ...